Better Work The Impact of Automation, Flexibilization and Intensification of Work - Kremer, Monique; Went, Robert; Engbersen, Godfried (Research for Policy, Studies by the Netherlands Council for Government Policy, 2021)
This is an Open Access book. How can we make work better? It is an important question, one that the Dutch government, employers' organizations and trade unions have been grappling with. People work to make money. But work also inspires self-respect, shapes our identity and gives us a sense of belonging - especially when the work we do is good. Good work is essential to prosperity in the broadest sense: to the quality of life we experience as individuals, to the economy and to society as a whole. Work in the Netherlands could be better. In Better Work. The automation, flexibilization and intensification of work, the Netherlands Scientific Council for Government Policy offers nine recommendations to help all workers gain more control over their money, their work and their lives - the three basic conditions of good work. While the primary responsibility for good work lies with employers, the government can help through legislation and regulations,supervision and subsidies, and through its tenders. .